Characterization and immune-modulatory roles of branched glucan and acetylated gluco-oligosaccharides produced by glucansucrase 40 from Leuconostoc mesenteroides YTU 40 - Dere, Sevda; Ispirli, Humeyra; Korkmaz, Kader; Tuncil, Yunus Emre; Sagdic, Osman; Narbad, Arjan; Ayyash, Mutamed; Dertli, Enes (NATURE PORTFOLIO, 2025)
Glucansucrases (GS) are functional enzymes for the production of distinct glucan and gluco-oligosaccharide structures with potential bioactive characteristics. In this study, an active glucansucrase (GS40) was identified within the genome of Leuconostoc mesenteroides YTU 40 that was further cloned, heterologously expressed and biochemically characterised. GS40 was capable of production of a branched dextran with similar to 20% (1 -> 3)-alpha-D-Glc residues detected by(1)H and(13)C NMR analysis. Acceptor reactions of GS40 with maltose and cellobiose were performed and distinct maltose/cellobiose derivative acetylated gluco-oligosaccharides were produced detected by TLC, NMR and LC-MS analysis. The bioactive characteristics of branched dextran and gluco-oligosaccharides were tested by determination of their immune-modulatory roles in terms of triggering IL-12, IL-10, IL-4 and TNF-alpha cytokine levels. These findings can be important to unveil the role of glucansucrases for the production of gluco-oligosaccharides that can be used as functional ingredients for food and other industries.
Keywords: BIOCHEMICAL-CHARACTERIZATION; ACCEPTOR REACTIONS; ALPHA; SUCROSE; FRUCTOOLIGOSACCHARIDES; POLYSACCHARIDES; Science & Technology - Other Topics